SUATU TINJAUAN PERANAN KEPALA DESA DALAM RANGKA PELAKSANAAN OTONOMI DAERAH MENURUT UU NOMOR 32 TAHUN 2004 DI DESA LENGGANG KABUPATEN BARITO SELATAN PROVINSI KAL – TENG - Bintara Bintara (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTThis raised the issue Impelentasi a review of the role of the village chief in the Context of Regional Autonomy Law No. According to. 32 of 2004 in the village of Lenggang, South Barito regency, Central Kalimantan province. The background of this research role of the village chief is expected to be able to advance his village along with BPD as legislative bodies at the village level.OBJECTIVE: To describe the procedure village chief duties under the Act No.. 32 of 2004, this study uses Juridical Empirical methods, field research and interviews, while the subject of research is the village chief in the village Lenggang, South Barito regency, Central Kalimantan Province.Research explains that happen on the field that the implementation of the role of the village chief in the village Lenggang running optimally, because the village chief in running the Government to establish a cooperative relationship in almost all institutions in the village Lenggang, South Barito regency, Central Kalimantan Province.